Phenotypic Characteristics of Human Bone Marrow-Derived Endothelial Progenitor Cells in vitro Support Cell Effectiveness for Repair of the Blood-Spinal Cord Barrier in ALS - Garbuzova-Davis, Svitlana (Brain Res, 2019)
Amyotrophic lateral sclerosis (ALS) was recently recognized as a neurovascular disease. Accumulating evidence demonstrated blood-spinal-cord barrier (BSCB) impairment mainly via endothelial cell (EC) degeneration in ALS patients and animal models. BSCB repair may be a therapeutic approach for ALS. We showed benefits of human bone marrow endothelial progenitor cell (hBMEPC) transplantation into symptomatic ALS mice on barrier restoration; however, cellular mechanisms remain unclear. The study aimed to characterize hBMEPCs in vitro under normogenic conditions. hBMEPCs were cultured at different time points. Enzyme-linked immunosorbent assay (ELISA) was used to detect concentrations of angiogenic factors (VEGF-A, angiogenin-1, and endoglin) and angiogenic inhibitor endostatin in conditioned media. Double immunocytochemical staining for CD105, ZO-1, and occludin with F-actin was performed. Results showed predominantly gradual significant post-culture increases of VEGF-A and angiogenin-1 levels. Cultured cells displayed distinct rounded or elongated cellular morphologies and positively immunoexpressed for CD105, indicating EC phenotype. Cytoskeletal F-actin filaments were re-arranged according to cell morphologies. Immunopositive expressions for ZO-1 were detected near inner cell membrane and for occludin on cell membrane surface of adjacent hBMEPCs. Together, secretion of angiogenic factors by cultured cells provides evidence for a potential mechanism underlying endogenous EC repair in ALS through hBMEPC transplantation, leading to restored barrier integrity. Also, ZO-1 and occludin immunoexpressions, confirming hBMEPC interactions in vitro, may reflect post-transplant cell actions in vivo.